Quizizz Application for Formative Assessment: Students' Perception - Kholid, Khoeriah; Wahidiyati, Irra (UM Purwokerto Press, 2025)
This research aims to analyze students’ perceptions of the Quizizz application in formative assessment at the 10th grade of MAN 2 Banyumas. This research employed a quantitative descriptive method, utilizing a questionnaire as the primary data collection technique. The questionnaire consisted of 30 items and was distributed to 370 respondents. The data is then presented in the form of a table after calculating the percentage of each statement. Then, the average rate of each part was calculated. The results of this research showed that students’ perception of the Quizizz application for formative assessment reached 77.5%, which, if classified, falls into the good category. Thus, it can be concluded that perception agrees with the statement. The results explained that Quizizz is an engaging tool that motivates students, promotes honesty and fairness, enhances understanding of material, and encourages teachers’ creativity through its various features, including question types, live modes, and online reports. The percentages of all these parts fall into the good classification, which means perception is generally accurate, although minor errors or limitations in understanding may occur.